2017
DOI: 10.3329/jsr.v9i3.31677
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Antibiogram of Bacterial Uropathogens of Urinary Tract Infections from a Tertiary Care Hospital of Bangladesh

Abstract: Urinary tract infections (UTIs) are one of the most frequently occurring infections majority of which are caused by multi-drug resistant (MDR) uropathogens. Hence, the present study was designed to find out the prevalence of bacterial pathogens causing UTIs and to determine their antibiotic resistance patterns against different classes of antibiotics. Cleancatch midstream urine samples were collected from 200 UTI patients of different sex and age groups. The uropathogens were isolated using Hi-Chrome UTI agar,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 25 publications
4
12
1
Order By: Relevance
“…The current study observed aerobic Gramnegative bacteria were the dominant pathogens with Enterobacteriaceae the predominant pathogens This finding was in agreement with previous studies study done by (Stefaniuk et al, 2016;Kumar et al, 2016 b) This result is in agreement with the previous studies of (Salunke and Gidamudi, 2017;Sanjee et al, 2017;Vranic et al, 2017;Wong et al, 2017) in which similar organisms were isolated, with E.coli was the most prevalent isolate…”
Section: Resultssupporting
confidence: 83%
“…The current study observed aerobic Gramnegative bacteria were the dominant pathogens with Enterobacteriaceae the predominant pathogens This finding was in agreement with previous studies study done by (Stefaniuk et al, 2016;Kumar et al, 2016 b) This result is in agreement with the previous studies of (Salunke and Gidamudi, 2017;Sanjee et al, 2017;Vranic et al, 2017;Wong et al, 2017) in which similar organisms were isolated, with E.coli was the most prevalent isolate…”
Section: Resultssupporting
confidence: 83%
“…The increase of MDR strains in this study may be the result of several reasons including overuse of antibiotics through their prescription or self-medication without antibiotic sensitivity testing, as well as sharing an antibiotic between family members or friends. Careless usage of antibiotics is the most important factor that facilitates the development of MDR, which triggers the selection and distribution of antibiotic-resistant pathogens in clinical practice [ 24 , 42 ]. To end this problem, Al-Hilali [ 24 ] and Lee et al [ 4 ] suggested that the antimicrobial therapy should be tailored to each patient, taking into consideration the severity of disease, individual and local patterns of antimicrobial resistance, and the potential for collateral damage associated with antimicrobial use.…”
Section: Discussionmentioning
confidence: 99%
“…UTI accounts for consumption of large proportion of anti-bacterial drugs [18]. Resistance to commonly prescribed antibiotics for UTI is an expanding global problem both in developed as well as developing countries [56]. UTI became quite alarming as isolated uropathogens exhibit high percentage resistance to almost all antibiotics [57].…”
Section: Drug-resistant Bacteria From Hiv Patientsmentioning
confidence: 99%